When campaigns can backfire: national identities and support for parties in the 2015 U.K. general election in Scotland - Morisi, Davide (2018)
Research on campaign strategies generally assumes that political parties avoid campaigning on issues that are internally divisive. However, this strategy might not always be viable, especially when parties attack each other in high-stake elections. This article provides novel evidence on the effects of campaigning on cross-cutting issues by focusing on the 2015 U.K. general election in Scotland. Results based on an experiment and a nationally representative survey show that the strategy to criticize the Scottish National Party (SNP) with regard to the cross-cutting issue of Scottish independence polarized voters along national identity lines. Among British voters, attack statements and perceived negativity increased support for some of the parties sponsoring the attacks, whereas among Scottish voters they actually increased support for the target of the attacks. In addition, experimental results indicate that attack statements affected mainly ideologically close parties (the Labour Party and the SNP). At the theoretical level, these findings indicate that the strategy to attack opposite parties on divisive issues can lead to both electoral gains and losses depending on voters$1 (3z(Bidentification(3y (Bwith such issues. - Reproduced.s
Keywords: Voting behaviour